Reconstruction, endocranial form and taxonomic affinity of the early Homo calvaria KNM-ER 42700. Issue 121 (August 2018) - Neubauer, Simon; Gunz, Philipp; Leakey, Louise; Leakey, Meave; Hublin, Jean-Jacques; Spoor, Fred
Abstract: When first described, the small calvaria KNM-ER 42700 from Ileret, Kenya, was considered a late juvenile or young adult and assigned to Homo erectus . However, this species attribution has subsequently been challenged because the specimen's neurocranial shape differs substantially from that of H. erectus adults. Here, (1) we describe the postmortem damage and deformation that could have influenced previous shape analyses, (2) present digital reconstructions based on computed tomographic scans correcting for these taphonomic defects, and (3) analyze the reconstructed endocranial shape and form, considering both static allometry among adults and ontogenetic allometry. To this end, we use geometric morphometrics to analyze the shape of digital endocasts based on landmarks and semilandmarks. Corroborating previous studies of the external surface, we find that the endocranial shape of KNM-ER 42700 falls outside the known adult variation of H. erectus . With an endocranial volume estimate between 721 and 744 ml, size cannot explain its atypical endocranial shape when static allometry within H. erectus is considered. However, the analysis of ontogenetic allometry suggests that it may be a H. erectus individual that is younger than previously thought and had not yet reached adult endocranial shape. Future work should therefore comprehensively review all cranial indicators of its developmental age, including closure of the spheno-occipital synchondrosis. An alternative hypothesis is that KNM-ER 42700 represents an as yet unidentified species of early Homo . Importantly, KNM-ER 42700 should not be included in the adult hypodigm of H. erectus .